2016
DOI: 10.24246/j.scholaria.2016.v6.i1.p117-126
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Supervisi Akademik Untuk Meningkatkan Kompetensi Guru Dalam Menyusun Administrasi Penilaian Di Sd Laboratorium Uksw

Abstract: <p>Tujuan penelitian tindakan kepala sekolah ini adalah untuk meningkatkan kompetensi pedagogik guru-guru di SD Laboratorium Salatiga dalam menyusun administrasi penilaian melalui supervisi akademik. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian tindakan sekolah. Kegiatan dalam penelitian ini terdiri atas tahapan perencanaan tindakan, pelaksanaan tindakan, observasi, dan refleksi.Teknik pengumpulan data menggunakan teknik obeservasi kelas.Instrumen observasi yang digunakan adalah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
2
9
0
5
Order By: Relevance
“…This is in accordance with the opinions of experts who revealed that supervision carried out by the school will help teachers to develop innovation and creativity they have. So as to be able to compete and be efficient in order to improve the quality of education (Amanda, Salam, & Saggaf, 2017;Astuti, 2016Astuti, , 2017Da'i, 2009;Farida, 2017;Syamsiar, Saggaf, Salam, & Ihsan, 2018) CONCLUSION Supervision of school principals has had a positive influence in order to improve the pedagogical competence of teachers at 237 Aletellue Elementary School in Soppeng Regency. This can be seen from every activity carried out by teachers who are able to improve creative and innovative competencies.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the opinions of experts who revealed that supervision carried out by the school will help teachers to develop innovation and creativity they have. So as to be able to compete and be efficient in order to improve the quality of education (Amanda, Salam, & Saggaf, 2017;Astuti, 2016Astuti, , 2017Da'i, 2009;Farida, 2017;Syamsiar, Saggaf, Salam, & Ihsan, 2018) CONCLUSION Supervision of school principals has had a positive influence in order to improve the pedagogical competence of teachers at 237 Aletellue Elementary School in Soppeng Regency. This can be seen from every activity carried out by teachers who are able to improve creative and innovative competencies.…”
Section: Discussionmentioning
confidence: 99%
“…This can help to improve the quality of learning, and increase teacher professionalism and competence. In addition, to improve competence, it is necessary to have academic supervision from the principal in preparing theadministration of the assessment (Astuti, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Academic supervision will control, direct, foster, and evaluate all teacher activities to achieve educational goals. The results of the evaluation of academic supervision will be used as input for teachers to improve the quality of education towards the best (Astuti, 2016). This study aimed to determine the contribution and effectiveness of the academic supervision of madrasah supervisors on the quality of education and the factors that influence the contribution of madrasah supervisors to education.…”
Section: Introductionmentioning
confidence: 99%